Neurology Concepts: Young Women and Ischemic Stroke—Evaluation and Management in the Emergency Department. (10th October 2017) - Chang, Bernard P.; Wira, Charles; Miller, Joseph; Akhter, Murtaza; Barth, Bradley E.; Willey, Joshua; Nentwich, Lauren; Madsen, Tracy
Abstract: Objective: Ischemic stroke is a leading cause of morbidity and mortality worldwide. While the incidence of ischemic stroke is highest in older populations, incidence of ischemic stroke in adults has been rising particularly rapidly among young (e.g., premenopausal) women. The evaluation and timely diagnosis of ischemic stroke in young women presents a challenging situation in the emergency department, due to a range of sex‐specific risk factors and to broad differentials. The goals of this concepts paper are to summarize existing knowledge regarding the evaluation and management of young women with ischemic stroke in the acute setting. Methods: A panel of six board‐certified emergency physicians, one with fellowship training in stroke and one with training in sex‐ and sex‐based medicine, along with one vascular neurologist were coauthors involved in the paper. Each author used various search strategies (e.g., PubMed, PsycINFO, and Google Scholar) for primary research and reviewed articles related to their section. The references were reviewed and evaluated for relevancy and included based on review by the lead authors. Results: Estimates on the incidence of ischemic stroke in premenopausal women range from 3.65 to 8.9 per 100, 000 in the United States. Several risk factors for ischemic stroke exist for young women including oral contraceptive (OCP) use and migraine with aura. Pregnancy and the postpartum period (up to 12 weeks) is also an important transient state during which risks for both ischemic stroke and cerebral hemorrhage are elevated, accounting for 18% of strokes in women under 35. Current evidence regarding the management of acute ischemic stroke in young women is also summarized including use of thrombolytic agents (e.g., tissue plasminogen activator) in both pregnant and nonpregnant individuals. Conclusion: Unique challenges exist in the evaluation and diagnosis of ischemic stroke in young women. There are still many opportunities for future research aimed at improving detection and treatment of this population.